Pengembangan Soal HOTS Matematika yang Mengintegrasikan Odi dan Umma Kalada di Kabupaten Sumba Barat Daya - Making, Samuel Rex Mulyadi; Napu, Timotius Woda (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Mathematics learning in schools can be conducted with a cultural approach to help students develop reasoning and problem-solving skills. This research is motivated by the low ability of students in Southwest Sumba in solving HOTS (Higher Order Thinking Skills) questions and other mathematics problems. Therefore, there is a need to develop contextual HOTS mathematics questions that are suitable for the local culture and customs. The objective of this research is to develop HOTS mathematics questions that integrate elements of Odi and Umma Kalada culture to be used in learning. The method used is development research with the stages: analysis, planning, development, implementation, and evaluation. In the analysis stage, data was obtained regarding the Odi and Umma Kalada cultures in Wanno Maredda Village, Laga Lete District, Southwest Sumba Regency. The planning stage was carried out to identify mathematical elements contained in both cultures, which were then designed into materials for HOTS questions. The development stage produced HOTS questions that are integrated with the local cultural context. Furthermore, in the implementation stage, a trial was conducted on the developed questions. The research results indicate that the culturally-based Odi and Umma Kalada mathematics HOTS questions were successfully developed and can be used as contextual and meaningful learning media for students.